Effect of GA3 and NAA on growth and yield of cabbage (Bangladesh Journal of Agricultural Research, 2019)
A field experiment was conducted at the Plant Physiology Field of Horticulture Research Center (HRC), Bangladesh Agricultural Research Institute, Gazipur during the rabi seasons of 2015-16 and 2016-17 to study the response of cabbage (var. Krishibid Hybrid-1 and Atlas-70) to foliar application of GA3 and NAA with different concentrations. The experiment was laid out in a Randomized Complete block Design with three replications. The experiment consisted of eight treatments viz., three levels of GA3 (at 50, 75 and 100 ppm) and four levels of NAA (at 40, 60, 80 and 100 ppm) along with distilled water as control. The varieties Krishibid Hybrid-1 and Atlas-70 were used in 2015-16 and 2016-17, respectively. Foliar spray of GA3 and NAA was given at 25 and 45 days after transplanting of seedling. The results of the investigation indicated significant differences among the treatments on most of the parameters studied. In Krishibid Hybrid-1, application of 50 ppm GA3 and 60 ppm NAA increased plant height, plant spread, number of leaves, chlorophyll content, head height, head diameter, single head weight without unfolded leaves as well as head yield (81.18 t/ha for 50 ppm GA3 and 78.57 t/ha for 60 ppm NAA) than the control (67.29 t/ha) and other treatments. But, in Atlas-70, application of 75 ppm GA3 gave the maximum values of most of the growth parameters, yield components and yield (102.40 t/ha), which was followed by 50 ppm GA3 (94.96 t/ha). In Krishibid Hybrid-1, application of 60 ppm NAA gave the highest benefit-cost ratio (BCR) of 3.63 followed by 75 ppm GA3 (3.59) while in Atlas-70, 75 ppm GA3 recorded the highest BCR of 4.79 followed by 50 ppm GA3 (4.54) and 60 ppm NAA (4.37). Therefore, application of GA3 @ 50-75 ppm or NAA @ 60 ppm concentration can be recommended for increasing the yield of cabbage with higher return.Bangladesh J. Agril. Res. 44(2): 367-376, June 2019